Efektivitas Biopot sebagai Media Pengomposan Sampah Organik Rumah Tangga: Studi Kuasi-Eksperimen - Iswanto Iswanto; Siti Hani Istiqomah; Catur Puspawati; Sepsiana Puspitasari (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
Global plastic production exceeds 320 million tons annually, with over 40% being single-use plastics. Indonesia generates approximately 7 million tons of waste annually, of which 4.9 million tons are poorly managed. Ineffective waste management necessitates specialized processing, such as composting using Biopot—biodegradable pots made from organic materials and waste—supporting sustainable agriculture and environmentally friendly waste management. This study employs a quasi-experimental design with a control group. Biopot made of plastic and earthenware are utilized for composting at depths of 60, 80, and 100 cm. The samples consist of 170 liters of organic waste collected from 50 households in Sukunan. Data analysis employs MANOVA to assess the effects of pot type and depth on compost quality. The highest average reduction in organic waste volume was observed in biopori (50.25%), followed by plastic Biopot (39.40%) and earthenware (38.05%). The quality of the compost met SNI standards, exhibiting neutral pH and appropriate C/N ratios. The plastic Biopot at 60 cm depth demonstrated the greatest effectiveness in compost production. Biopot successfully reduces organic waste by 39.40% (plastic) and 38.05% (earthenware), yielding compost that meets SNI standards. The plastic Biopot at a depth of 60 cm is the optimal choice for household organic waste composting.